Kajian Terhadap Risiko Pada Jual Beli Benda Bergerak - Bing Waluyo (Faculty of Law, Universitas Wijayakusuma, 2022)
Risk is the obligation to bear losses as a result of an event (event) that befalls the object of the agreement beyond the fault of one of the parties. Based on this understanding, it can be seen that the issue of risk stems from the occurrence of events beyond the fault of one of the parties to the agreement. This event in contract law is called a state of coercion (overmacht; force majeure). Thus, the issue of risk is the aftermath of the problem of coercive circumstances (overmacht; force majeure), which is an event that is unintentional, cannot be predicted or known, and is beyond the power of the compelling debtor. When viewed from the type, the state of coercion can be divided into two, namel An absolute/absolute force majeure situation, and A situation of compulsion (overmacht; force majeure) that is relative, Regarding the risks in buying and selling movable objects, in the Civil Code there are three regulations, namely Regarding certain objects (Article 1460 of the Civil Code), Regarding objects sold according to weight, quantity or size (Article 1461), and Regarding the objects for sale which are sold according to piles (Article 1462). Based on Article 1462 of the Civil Code, the risk of the object lies with the buyer. Keywords: Risk, Buying and Selling, Moving Objects. Risiko adalah kewajiban untuk menanggung kerugian sebagai akibat dari adanya suatu peristiwa (kejadian) yang menimpa obyek perjanjian di luar kesalahan salah satu pihak. Berdasarkan pada pengertian tersebut, dapat diketahui bahwa persoalan risiko berpokok pangkal pada terjadinya peristiwa di luar kesalahan salah satu pihak yang mengadakan perjanjian. Peristiwa tersebut dalam hukum perjanjian disebut dengan keadaan memaksa (overmacht; force majeur). Dengan demikian, persoalan risiko merupakan buntut dari persoalan keadaan memaksa (overmacht; force majeur), yaitu suatu peristiwa yang tidak disengaja, tidak dapat diduga atau diketahui, dan di luar kekuasaan si debitur yang memaksa. Jika dilihat dari macamnya, keadaan memaksa dapat dibagi menjadi dua, yaitu Keadaan memaksa (overmacht; force majeur) yang bersifat absolut/mutlak, dan Keadaan memaksa (overmacht; force majeur) yang bersifat relatif/nisbi, Mengenai risiko pada jual beli benda bergerak, di dalam KUH Perdata terdapat tiga peraturan, yaitu Mengenai benda tertentu (Pasal 1460 KUH Perdata), Mengenai benda yang dijual menurut berat, jumlah atau ukuran (Pasal 1461), dan Mengenai benda yang dijual yang dijual menurut tumpukan (Pasal 1462). Berdasarkan pada Pasal 1462 KUH Perdata, risiko atas benda tersebut berada di pihak pembeli. Kata kunci: C Risiko, Jual Beli, Benda Bergerak.